Interventional bronchoscopy from Killian to gene therapy - Bolliger, Christoph T.; Mathur, Praveen N. (Karger, 2000)
This book covers all aspects of diagnostic and therapeutic bronchoscopy, which go beyond the techniques of inspection, simple lavage and biopsies of the tracheobronchial tree. In a first section, historical aspects as well as the modern use of both rigid and flexible instruments, the set-up of a bronchoscopy unit, anaesthetic techniques, and functional evaluation for patients undergoing interventional bronchoscopy are discussed. A diagnostic section on transbronchial needle aspiration and bronchoscopic ultrasound is followed by extensive coverage of all existing therapeutic techniques: foreign body removal, laser resection, electrocautery, argon plasma coagulation, cryotherapy, brachytherapy, photodynamic therapy, stenting, and a chapter on multi-modality treatment of advanced pulmonary malignancies. A fourth section deals with percutaneous image-guided procedures, percutaneous dilatational tracheostomy, and transtracheal oxygen therapy. The last section provides an in-depth look at emerging bronchoscopic technology, such as autofluorescence, virtual bronchoscopy, and gene therapy.Written by the world's leading authorities in the field and beautifully illustrated, this book presents the state of the art of interventional bronchoscopy. It is recommended reading for pulmonologists, thoracic or ENT surgeons, oncologists and physicians who take an interest in bronchoscopy
Keywords: Respiratory System; Oncology; Thoracic Surgery; Bronchoskopie; Aufsatzsammlung